Copper‐Catalyzed Synthesis of Tetrasubstituted Allenes from Quaternary Ammonium Salts and Grignard Reagents. Issue 9 (17th February 2017) - Ma, Shengming; Liu, Qi; Tang, Xinjun; Cai, Yujuan
Abstract: Although the synthesis of allenes has made considerable progress, methods for tetrasubstituted allenes are still limited. In this paper, the CuBr2 ‐catalyzed cross‐coupling reaction of Grignard reagents and propargylic ammonium salts in tetrahydrofuran at 60 °C under argon delivered tetrasubstituted allenes in good to excellent yields. The reaction is thought to proceed by an SN 2′ pathway. Abstract : Copper proves its worth : Tetrasubstituted allenes have been prepared from the CuBr2 ‐catalyzed reaction of readily available quaternary ammonium salts and Grignard reagents. The reaction proceeds smoothly giving products in good to excellent yields (see scheme).